2011
DOI: 10.1051/0004-6361/201015896
|View full text |Cite
|
Sign up to set email alerts
|

2D radiative-magnetohydrostatic model of a prominence observed by Hinode, SoHO/SUMER and Meudon/MSDP

Abstract: Aims. Prominences observed by Hinode show very dynamical and intriguing structures. To understand the mechanisms that are responsible for these moving structures, it is important to know the physical conditions that prevail in fine-structure threads. In the present work we analyse a quiescent prominence with fine structures, which exhibits dynamic behaviour, which was observed in the hydrogen Hα line with Hinode/SOT, Meudon/MSDP and Ondřejov/HSFA2, and simultaneously in hydrogen Lyman lines with SoHO/SUMER dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
28
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 22 publications
6
28
0
Order By: Relevance
“…We start our investigation with the Model2, which was found by Berlicki et al (2011) to produce synthetic Lyman spectra in good agreement with observations (see Fig. 9).…”
Section: Synthetic Datasupporting
confidence: 56%
See 4 more Smart Citations
“…We start our investigation with the Model2, which was found by Berlicki et al (2011) to produce synthetic Lyman spectra in good agreement with observations (see Fig. 9).…”
Section: Synthetic Datasupporting
confidence: 56%
“…This appears to be in conflict to the findings of Schmieder et al (2007), who showed that the Lyman line profiles obtained with the LOS perpendicular to the magnetic field exhibit a central reversal, while those obtained with a LOS parallel to the field show the nonreversed profile shape. However, as discussed by Berlicki et al (2011) and Gunár et al (2011b), this dependance of the Lyman line profile shape on the orientation of the LOS is valid only for models of sufficiently high mass. In the case of low-mass, lowpressure models such as Model2 or Model_DEM (Gunár et al 2011b), even the Lyman lines obtained with LOS perpendicular to the magnetic field exhibit non-reversed profiles.…”
Section: Synthetic Datamentioning
confidence: 99%
See 3 more Smart Citations